Bibliometric-Based Evaluation of the Neuromarketing Research Trend: 2010–2021 - Zhu, Zeren; Jin, Yuanqing; Su, Yushun; Jia, Kan; Lin, Chien-Liang; Liu, Xiaoxin (Frontiers in Psychology, 2022)
Neuromarketing is a new and important topic and method in the field of marketing in recent years. Because of the research on consumer behavior, it has been paid more and more attention. In the past decade, the importance of marketing has also been valued by many fields, such as consumer behavior, advertising, information systems, and e-commerce. In particular, neuromarketing uses neurological methods to determine the driving force behind consumers' choices. Various neuroscience tools, such as eye movements, are adopted to help reveal how they react to particular advertisements or objects. Such information can be used as the basis for new advertising campaigns and brand promotion. Of course, in order to effectively explore the research trends in this field, we must understand the current situation of neuromarketing. This study analyzed the related literature application of neuromarketing from 2010 to 2021 and referred to 20 three-star journals published by Association of Business Schools in the field of marketing in 2021 as the main analysis basis. Based on the data collected by WOS, this study mainly collected 119 references and analyzed the most productive countries, universities, authors, journals, and prolific publications in the field of neuromarketing by Citespace. Through the analysis of knowledge map, this study explored the mapping of co-citation, bibliographic coupling (BC), and co-occurrence (CC) and probed into the development process of the discipline every five years. This study provided an overview of the trends and paths of neuromarketing, which can help researchers understand the global trends and future research directions.